Analysis of the Effectiveness of Drug Management Systems in Tangerang Selatan General Hospital in 2021: Analisis Efektivitas Sistem Pengelolaan Obat di Rumah Sakit Umum Tangerang Selatan Tahun 2021 - Zaafira, Reyhan Diva; Yardi, Yardi (Universitas Tadulako, 2024)
Background: Pharmaceutical services are closely related to an optimal drug management system, where with optimal drug management, drug availability can be guaranteed, and patient demand can be fulfilled. Objectives: This study aimed to analized the effectiveness of the drug management system at the distribution stage at the Tangerang Selatan General Hospital in 2021. Material and Methods: The method used wasbased on a book by Satibi in the form of percentage of compatibility of drugs with drug stock cards, Turn Over Ratio (TOR), drug availability levels, percentage of expired and damaged drugs, and percentage of dead stock as measured usedstandards. Data taken prospectively for compatibility of drugs with drug stock cards, and retrospectively for other indicators by looking at generic drug stock cards in 2021. Results: The results showed that the drug compatibility indicators with drug stock cards and the level of availability of drugs were in accordance with the standards, while the Turn Over Ratio (TOR) and dead stock indicators did not meet the standard indicators. Conclusions: The drug management system at the South Tangerang City General Hospital can still be improved.